Soil Erosion in the Rameswaram Island - Wilson, J. (Indian Forester, 1965)
The paper reviews the various forms of erosion prevalent in the Rameswaram island and their causes. Soil conservation methods to combat them are suggested with emphasis on the planting of Casuarina wherever the soil and water conditions permit its propagation, in view of its great economic importance in the region having acute fuel shortage, apart from its soil binding properties. Introduction of other species combined with other soil conservation methods arc suggested for areas not presently suitable for Casuarina. These include the use of modern petroleum emulsions for fixing shifting sand, draining of water from inland depressions where water stagnates, etc., combined with afforestation by species suitable for each type of soil and terrain with the ultimate object of arresting the erosion menace.